Multimodal Discourse Analysis on Mathematics Instruction: A Case Study in Indonesian Primary School - Healty Susantiningdyah; Ulfa Kurnia; Winarni Winarni; Alfi Suci Dirgantari (English Learning Innovation (englie), 2022)
Mathematics has been taken into account as one of the prominent subjects in various levels of formal education. The most common issues related to learning mathematics are more likely perceived by students in primary schools as they begin to develop their critical literacy skills, including mathematics register, calculation, concepts, and principles. Therefore, this research aimed at (1) identifying types of multimodal texts used for mathematics instruction and (2) knowing how semiotic resources create meaning in terms of the mathematical concept. The research setting was SDN 08 Sei Wain, Balikpapan Utara, East Kalimantan participated by the fifth-grade students. The data collection procedure included observation and questionnaires, while data analysis was derived qualitatively. The result of the research was expected to be an insightful reference for primary teachers, policymakers, and stakeholders to improve the quality of learning in primary education.